Trianon és a nemzetközi jog - Szávai, Ferenc (Közép-Európai Közlemények, 2010)
The development of international law brought considerable results in the area of state succession, both with respect to contracts and public debt. Peace treaties regulated the disintegration of both the Austro-Hungarian Empire and the Ottoman Empire. Although the Peace Treaty of Trianon was in many ways vague, it regulated the issues of properties and public debt. The study gives an account of this process.